Is endolymphatic hydrops, as detected in MRI, a truly cochleocentric finding? - Álvarez De Linera-Alperi, Marta; Dominguez, Pablo; Blanco-Pareja, Melissa; Menéndez Fernández-Miranda, Pablo; Manrique-Huarte, Raquel; Liaño, Gloria; Pérez-Fernández, Nicolas; Suárez-Vega, Víctor (Frontiers in Neurology, 2024)
IntroductionThe most common histopathological finding in Ménière’s disease (MD) is endolymphatic hydrops (EH), which involves the dilation of the membranous labyrinth. The direct relationship between EH and MD is debated, although EH plays a crucial role in auditory and vestibular functional tests. MRI sequences such as 3D-FLAIR and 3D-real-IR are used to study EH, with the latter being more effective. This study aimed to examine whether the severity of EH detected by MRI is always more pronounced in the cochlea than in the vestibule, indicating a cochleocentric progression of the condition.MethodsA retrospective longitudinal study was conducted at a tertiary care medical center from 2019 to 2023, involving patients diagnosed with unilateral Ménière’s disease. All patients underwent MRI hydrops assessments (3D-REAL-IR sequences) using 3 Tesla magnets and gadobutrol contrast agent. EH was graded qualitatively and quantitatively for both ears using scales for cochlear endolymphatic hydrops (cEH) and vestibular endolymphatic hydrops (vEH). Volumetric measurements of the vestibule and endolymph were performed, and the vestibular endolymphatic ratio (vELR) was calculated. The degree of perilymphatic enhancement (PE) and endolymphatic herniation was also assessed. Patient data, including demographics, disease features, comorbidities, hearing loss, and vestibular function, were collected from medical records. Statistical analysis involved various tests to compare groups and evaluate correlations, using a significance level of p < 0.05. The study aimed to classify the patients into cochleocentric (CC) or non-cochleocentric (NCC) groups based on the difference in the severity of EH in both compartments.ResultsWe included 137 patients, of whom 55 (40.15%) were classified as CC, and the remaining 82 (59.85%) were classified as NCC. The degree of vestibular EH (vEH) was more severe in the NCC group (p < 0.001), while cochlear EH (cEH) showed a moderate correlation with vEH. The mean vestibular endolymphatic ratio (vELR) was higher in the NCC group (80.5% ± 38%) compared to the CC group (55% ± 49.5%) (p < 0.0001). Vestibular herniation was more common in the NCC group, while vestibular perilymphatic enhancement was more prevalent in the CC group. Cardiovascular risk was associated with the CC group, while the NCC group reported more vestibular symptoms. Delayed Ménière’s disease was linked to the CC group. The hearing loss and vestibular function tests did not show significant differences between the groups.DiscussionIn conclusion, our study found that endolymphatic hydrops (EH) was more severe in the vestibule than in the cochlea in nearly 60% of the cases, with a clinical correlation to the initial symptoms. However, no significant differences were observed in the auditory or vestibular function tests during the follow-up.V Previous studies have indicated that vestibular EH occurs early in Ménière’s disease (MD) and subsequently progresses to the cochlea, a finding that challenges the traditional cochleocentric progression theory supported by experimental and clinical otopathology. MRI techniques have enhanced the detection of EH, revealing that the relative amount of endolymph is slightly higher in the vestibule than in the cochlea, thereby supporting the study’s findings. We considered the important technical limitations in the MRI visualization of EH and suggested that advanced imaging techniques and volumetric quantification could enhance the classification of cochleocentric and non-cochleocentric groups. The clinical findings revealed that cardiovascular risk factors and delayed MD phenotypes were more common in the cochleocentric group, while the non-cochleocentric group exhibited poorer vestibular MRI results and a higher incidence of endolymph herniation into the semicircular canals.